The journey towards social exclusion in Colombia - Guevara Fletcher, Diego Andrés; Guevara Corral, Rubén Darío (Inglaterra, 2010)
There has been continuing forced displacement over many years in the south of the Department of Valle del Cauca in Colombia. Families fleeing conflict and violence between insurgents and government forces have moved into the municipality of Florida which has a population of approximately 55,000. Having lost the economic, social, cultural and symbolic capital accumulated in their home areas, they struggle to compensate for these losses and to preserve or improve on their well-being and living conditions.

Ha habido desplazamientos forzados continuos durante muchos años en el sur del Departamento del Valle del Cauca en Colombia. Las familias que huyen del conflicto y la violencia entre los insurgentes y las fuerzas gubernamentales se han trasladado al municipio de Florida, que tiene una población de aproximadamente 55.000 habitantes. Habiendo perdido el capital económico, social, cultural y simbólico acumulado en sus zonas de origen, luchan por compensar estas pérdidas y por preservar o mejorar su bienestar y sus condiciones de vida.
Keywords: Colombia - Aspectos sociales; Desplazamiento forzado - Colombia; Pobreza - Colombia; Desempleo - Colombia; Colombia - Social aspects; Forced displacement - Colombia; Poverty - Colombia; Unemployment - Colombia